The Effectiveness of a Proposed Study Module in Geography Based on Green Economy in Providing Fifth Graders with the Concepts Associated with it and Developing Their Environmental Awareness - Mousa, Rajaa Mohammed Ahmed (Dirasat: Educational Sciences, 2024)
Objectives: The study aimed to explore the effectiveness of a proposed unit in geography based on the green economy in imparting related concepts to fifth-grade students and enhancing their environmental awareness. Methods: The researcher used a quasi-experimental approach. The experimental tools, which included the proposed unit and the teacher's guide, were designed. Measurement tools were prepared, consisting of a green economy concepts test at various levels and an environmental awareness scale that included three components: cognitive, affective, and behavioral. These experimental and measurement tools were applied to a sample of 40 students who were selected randomly, and the data were statistically analyzed. Results: The results demonstrated a significant effectiveness of the proposed unit in developing green economy concepts and environmental awareness among the study sample. The overall effect size was 0.875 and 0.886 for the green economy concepts test and the environmental awareness scale, respectively. A statistically significant difference at the α ≤ 0.01 level was found between the mean scores of the fifth-grade students in the pre-test and post-test applications of the green economy concepts test and the environmental awareness scale, in favor of the post-test application. Conclusions: The study recommended the necessity of including the green economy concepts presented during the current study in geography curricula to varying degrees of depth and precision, according to the nature of the levels at different educational stages. It also emphasized connecting learners to their surrounding environment through environmental service projects and promoting correct behavior towards it to enhance their environmental awareness.